Study on sandy beach morphological changes during dry and wet season at Desaru, Johor - Nur Raudzah Fasahah, Abdul Wahab (2015)
The Peninsular Malaysia experienced two seasonal changes which known as Northeast monsoon (wet season) which normally occur from November to March and Southwest monsoon (dry season) starting from May to August. This seasonal variations has been believed as the main factors for the changes in the beach profile which significantly caused erosion to occur during wet season while accretion is tend to happen during dry season. The aim of this study is to investigate the relationship between the seasonal variations to beach profile changes This study was conducted at Desaru beach, Johor. Desaru beach can be classified as a sandy beach because it consist of fine sand range from 0.4 to 0.8 mm. The rainfall data during this two seasons was collected together with the sample of sand and the beach profile of the study area in order to determine the relationship between the rainfall depth during the seasonal variations, the moisture content in the sand and the beach profile changes. The data was collected from May 2014 until February 2015. One rain gauge was installed at the study area to collect the rainfall data. For the beach profiles, the total station was used to do the survey works. The results indicates that during the wet season from November to March, the rainfall depth was higher compared to the dry season from May to August. The seasonal variations is the factor that affect the changes in beach profile. It is clearly shown by the total amount of the rainfall depth according to the monthly data from May 2014 until March 2015 which significantly increased and decreased in the wet and dry period, respectively. From this study also, it is found that the higher rainfall depth caused the temperature to decrease and when the rainfall depth is lower or when there were no rainfall receive, the temperature increased. High and low rainfall depth during dry and wet seasons also lead to increase and decrease in groundwater which caused the beach profile to change. This explains why erosion tend to occur during wet season and accretion tend to occur during dry season.